Principal Leadership Behaviour in Improving Education Quality at SDN Cigugur Tengah Mandiri 2 - Sapitri, Riris; Eka Cipta, Samudra (Samsara Institute Publisher, 2025)
SDN Cigugur Tengah Mandiri 2 is a favorite school in Cigugur Tengah Village, Cimahi City, West Java. In this school, there are various academic and non-academic activities, qualified and experienced teaching staff, adequate school facilities that are clean and comfortable, various achievements at the city and provincial levels, and good environmental management. This study aims to determine and describe the leadership behavior of school principals in improving the quality of education at SDN Cigugur Tengah Mandiri 2. This research uses a descriptive qualitative approach. The research informant was the principal. Selection of informants using a purposive sampling technique. Data were collected through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results showed that the leadership behavior of school principals in improving the quality of education is good, this can be seen in resource management, professional development, collaboration, communication, decision-making, monitoring, and school culture.